BedSect: An Integrated Web Server Application to Perform Intersection, Visualization, and Functional Annotation of Genomic Regions From Multiple Datasets - Mishra, Gyan Prakash; Ghosh, Arup; Jha, Atimukta; Raghav, Sunil Kumar (Frontiers in Genetics, 2020)
A large number of genomic regions captured from next generation sequencing (NGS) data analyses or publically available transcription factor binding sites from ENCODE are generally overlapped to answer a variety of biological questions. Though several command-line tools are available to perform such analysis, an integrated web server application that can perform the genomic region intersections from multiple datasets, then to generate plots depicting subsets of the overlapped regions and perform integrated functional annotation was lacking. To address this gap, we have developed a comprehensive user-friendly web server application i.e. BedSect, where users can upload genomic regions from multiple datasets or select BED file from integrated Gene Transcription Regulation Database GTRD datasets, without any file number limitation to perform intersection analysis along with visualization of the intersection regions as UpSet and Correlation plot using integrated Shiny application. BedSect also integrates GREAT tool for functional annotation, gene ontology, and biological pathways enrichment analysis for the identified unique and intersected genomic regions. These intersecting genomic regions can be further uploaded in the UCSC genome browser using a hyperlink inbuilt in the tool for visualization of the results as custom tracks. BedSect is available at http://imgsb.org/bedsect/.